Carbon Leakage: A Medium- and Long-Term View - Florian Habermacher (Center for Economic Studies and ifo Institute (CESifo), 2015)
Future market developments determine the fate of fossil fuel carbon currently conserved unilaterally. Dynamic fuel depletion naturally suggests leakage rates approaching 100%. Reasons for lower leakage differ from what limits rates in previous studies. Discounting reduces present-value leakage as global emissions are delayed. Containing climate change requires future global political or technological breakthroughs to conserve some carbon forever. Early breakthroughs limit leakage but with late breakthroughs most unilateral emission reductions may be negated abroad. Future coal liquefaction suggests negative leakage rates for current mitigation, but a perfect backstop allows leakage above unity. Leakage rates and suggested taxes vary across fuels.
Keywords: Q54; Q41; H23; H21; 330; unilateral climate policy; emission impulse response; fossil fuel depletion; dynamic carbon leakage; discounting; fuel specific carbon tax; coal liquefaction; backstop; OECD